India : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
This paper presents background information to the assessment of competitiveness and exchange rate policy in India, as well as challenges to monetary policy from financial globalization. This paper discusses the role of communication in enhancing the effectiveness of monetary policy and strengthening the financial system in India. Currency derivatives can provide important benefits for financial systems. This paper aims to document the extent to which Indian growth has benefited the bottom of the income distribution and how India can achieve significantly better social outcomes.